2015
DOI: 10.3390/rs71013436
|View full text |Cite
|
Sign up to set email alerts
|

Scale Issues Related to the Accuracy Assessment of Land Use/Land Cover Maps Produced Using Multi-Resolution Data: Comments on “The Improvement of Land Cover Classification by Thermal Remote Sensing”. Remote Sens. 2015, 7(7), 8368–8390

Abstract: Much remote sensing (RS) research focuses on fusing, i.e., combining, multi-resolution/multi-sensor imagery for land use/land cover (LULC) classification. In relation to this topic, Sun and Schulz [1] recently found that a combination of visible-to-near infrared (VNIR; 30 m spatial resolution) and thermal infrared (TIR; 100-120 m spatial resolution) Landsat data led to more accurate LULC classification. They also found that using multi-temporal TIR data alone for classification resulted in comparable (and in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 16 publications
(28 reference statements)
1
16
0
Order By: Relevance
“…In a subsequent comment, Johnson [3], surprised by the high accuracy they obtained (up to 99% OA with four classes) and by the contrast between their findings and those of other recent research, correctly identified a flaw in the accuracy assessment, namely the lack of independence between training and validation pixels. In essence, the authors, who had delineated a number of individual polygons of each class for use as 'ground truth' (446 polygons in total, of 5 ha mean size), were separating reference pixels into training (90%) and validation (10%) in a way that placed most validation pixels adjacent to training pixels, which in the case of the thermal band meant that they had overlapping footprints.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…In a subsequent comment, Johnson [3], surprised by the high accuracy they obtained (up to 99% OA with four classes) and by the contrast between their findings and those of other recent research, correctly identified a flaw in the accuracy assessment, namely the lack of independence between training and validation pixels. In essence, the authors, who had delineated a number of individual polygons of each class for use as 'ground truth' (446 polygons in total, of 5 ha mean size), were separating reference pixels into training (90%) and validation (10%) in a way that placed most validation pixels adjacent to training pixels, which in the case of the thermal band meant that they had overlapping footprints.…”
Section: Introductionmentioning
confidence: 96%
“…There were other relevant issues in the accuracy assessment of [2] beyond that pointed out in [3]. Regrettably, I suspect this is more the norm than the exception: I speculate that if we randomly picked a sample of recent articles describing land cover mapping efforts and scrutinized their accuracy assessments, the majority would have some issue, or at least incomplete information to judge if there are issues.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, to extract different land cover classes, it is more reasonable to use multiple SPs, each of which is appropriate for a separate land cover class. Such a multi-scale/level approach can positively affect the quality of extraction of different land cover classes, and thus can improve the accuracy of final classification results, as reported in several studies [17][18][19][20].…”
mentioning
confidence: 97%
“…
Abstract: Following the suggestion made by Johnson (Johnson B.A., 2015), a polygonbased cross validation (CV) method is compared to the pixel-based CV method to classify different levels of land cover categories using a single-date Landsat 8 image and time series of Landsat TM images. Also, different variants of band combinations, with and without the thermal bands, were considered.
…”
mentioning
confidence: 99%